Intimacy, contraception, and pregnancy prevention in patients with pulmonary arterial hypertension: are we counseling our patients?. (1st October 2020) - Hill, Wendy; Holy, Royanne; Traiger, Glenna
Abstract : Pulmonary arterial hypertension (PAH) is a serious, life‐altering condition. Patients who are diagnosed are often of childbearing potential. Given the well‐documented risks associated with this condition during pregnancy, as well as risks to the fetus from medications used to treat this disorder, patients should be strongly advised against pregnancy. Despite this, patients still become pregnant, leading to the question of whether care providers are counseling patients and their partners about the risks of pregnancy, methods of contraception, and issues of intimacy on a regular basis. We have conducted a survey of pulmonary hypertension specialist physicians and allied healthcare professionals on their practice patterns related to counseling on intimacy, contraception, and pregnancy prevention. Most respondents indicated they are counseling on these issues to varying degrees, but our survey pointed to several areas where improvements can be made. The most significant barrier to counseling for all respondents was lack of time. Survey respondents reported that a large percentage of the pregnancies seen in their practices were either intentional or due to contraceptive non‐compliance. We review specific practical approaches to initiate reproductive health counseling as well as ways to integrate this important aspect of PAH care into regular practice routines and documentation. Protocols regarding pregnancy avoidance and PAH should be developed and become standard procedure.